Avaliação da penetração, coesão, aderência e desgaste superficial de ligantes alternativos e comerciais para aplicação na imprimação betuminosa de rodovias - Almeida, Fernando Dácio de (2017)
In Brazil, the cutback of Medium Cure (CM-30) is usually used for bituminous primer services. In developed countries, there has been a greater restriction on the use of the CM-30 in the primer because it is considered damaging to the environment due to the very manipulation of bituminous material as well as the emission of volatile organic hydrocarbons. In the pavement area, little information is available on the behavior of commercial and alternative products for the use in bituminous primer services, the need to develop studies on alternative materials, less polluting cutbacks that may in the future replace the CM- 30. The general objective of this research was to investigate the behavior of commercial cutbacks and alternative cutbacks for the use in services of bituminous primer. For this purpose, the parameters of penetration, cohesion, adhesion and surface wear of a primed base with sandy soil were evaluated using: (i) a commercial reference cutback of type CM-30, (ii) An alternative cutback produced in the laboratory from the blend of a CAP with D-limonene, a vegetable oil obtained from citrus peel; and (iii) three commercial cutbacks. In general, for the sandy base tested, the alternative cutback with D-limonene showed promising results when compared to reference and commercial cutbacks for all evaluated parameters. It was concluded that the alternative cutback may represent an environmental friendly alternative using vegetable oil as solvent instead of the solvent used in CM-30 production.